The Impact of Homogeneous Versus Heterogeneous Emphysema on Dynamic Hyperinflation in Patients With Severe COPD Assessed for Lung Volume Reduction. (2nd November 2015) - Boutou, Afroditi K.; Zoumot, Zaid; Nair, Arjun; Davey, Claire; Hansell, David M.; Jamurtas, Athanasios; Polkey, Michael I.; Hopkinson, Nicholas S.
Abstract: Dynamic hyperinflation (DH) is a pathophysiologic hallmark of Chronic Obstructive Pulmonary Disease (COPD). The aim of this study was to investigate the impact of emphysema distribution on DH during a maximal cardiopulmonary exercise test (CPET) in patients with severe COPD. This was a retrospective analysis of prospectively collected data among severe COPD patients who underwent thoracic high-resolution computed tomography, full lung function measurements and maximal CPET with inspiratory manouvers as assessment for a lung volume reduction procedure. ΔIC was calculated by subtracting the end-exercise inspiratory capacity (eIC) from resting IC (rIC) and expressed as a percentage of rIC (ΔIC %). Emphysema quantification was conducted at 3 predefined levels using the syngo PULMO-CT (Siemens AG); a difference >25% between best and worse slice was defined as heterogeneous emphysema. Fifty patients with heterogeneous (62.7% male; 60.9 ± 7.5 years old; FEV1 % = 32.4 ± 11.4) and 14 with homogeneous emphysema (61.5% male; 62.5 ± 5.9 years old; FEV1 % = 28.1 ± 10.3) fulfilled the enrolment criteria. The groups were matched for all baseline variables. ΔIC% was significantly higher in homogeneous emphysema (39.8% ± 9.8% vs.31.2% ± 13%, p = 0.031), while no other CPET parameter differed between the groups. Upper lobe predominance of emphysema correlated positively with peak oxygen pulse, peak oxygen uptake and peak respiratory rate, and negatively with ΔIC%. Homogeneous emphysema is associated with more DH during maximum exercise in COPD patients.